Experimental and theoretical study of size-dependent phase evolution in NaCl-KCl alloys - Sumeet Kumar; Shashank Shekhar Mishra; Niladri Naskar; Suman Sarkar; Sanjay Kashyap; Nirmal Kumar Katiyar; Manas Paliwal; Krishanu Biswas; C.S. Tiwary; Kamanio Chattopadhyay (Next Materials)
In the present investigation, the formation of nanocrystalline bi-alkali halide (NaCl+KCl) obtained by combined low temperature (cryomilling) with room temperature (RT) milling was reported. The cryomilling, which is endowed with special ability to accelerated fracture and form free ionic salt crystals, is utilized for rapid refinement. This is followed by RT milling to form biphasic nanocrystallites. The bi-phase formation with the time of milling was characterized using a scanning electron microscope (SEM) and transmission electron microscope (TEM). The change in lattice parameter and introduction of micro-strain in the lattice (due to cold work and bi-phase formation) have been characterized using X-ray diffraction and deduce using theoretical calculations. The investigation reveals the influence of milling time on the shape and size of the crystallites along with formation of biphasic NaCl-KCl crystallites with inner core being NaCl surrounded by KCl crystals. The KCl powder particles get deposited on the surface of NaCl crystals to maintain the charge neutrality during ball milling. The shape of NaCl undergoes change from cuboid to cuboctahedron with the progression of milling time due to plastic deformation induced roughing. The temperature-dependent mechanical behaviour and associated mechanism of the milled NaCl-KCl system were discussed and supported by the thermodynamic modal. It is evident, NaCl-KCl is phase separating system, which accentuated at nanosized and hence, the formation of biphasic crystalline structure is observed during combined cryo and RT milling.